80.6k views
4 votes
Please help...

(02.03) The table shows the solution to the equation
|2x − 4| − 3 = 3:
Step 1 |2x − 4| = −3 + 3
Step 2 |2x − 4| = 0
Step 3 2x − 4 = 0
Step 4 2x = 4
Step 5 x = 2
Which is the first incorrect step? (1 point)
Select one:
a. Step 1
b. Step 2
c. Step 3
d. Solution is correct

1 Answer

1 vote

Answer:

a. Step 1

Explanation:

When solving equations, in order to isolate the variable (get the 'x' by itselt), you need to use inverse (opposite) operations. In the equation:

l2x - 4l - 3 = 3

Step 1: l2x - 4l = -3 + 3 *this step is incorrect because the inverse of subtraction is addition so the '-3' should be added to both sides:

l2x - 4l - 3 + 3 = 3+ 3

Step 2: l2x - 4l = 6

Step 3: 2x - 4 = 6

Step 4: 2x = 10

Step 5: x = 5

User Omer Maki
by
5.8k points